Analisis Hubungan Kemampuan Manajemen Konflik Kepala Ruangan dengan Kepuasan Kerja Perawat Pelaksana di Ruang Rawat Inap Rumah Sakit Tk. III Reksodiwiryo Padang : Analysis of the Relationship between the Conflict Management Ability of the Head of the Room with Job Satisfaction of Implementing Nurses in the Inpatient Room Hospital Tk. III Reksodiwiryo Padang - Astri Doris; Fatma Sriwahyuni; Vetty Priscilla (Fakultas Keperawatan Universitas Andalas, 2019)
Some negative impacts that can be caused by conflicts include the decrease of work productivity, such as affecting teamwork relationships that have an impact on job satisfaction of implementing nurses, and the process of service activities undertaken is hampered. The purpose of this study was to analyze the relationship between conflict management of the head nurse of the room with the work satisfaction of implementing nurses. This type of research is quantitative research with cross sectional approach. The sampling technique was proportional random sampling with a sample size of 83 people. The results of the study were obtained. There is a significant relationship between conflict management and job satisfaction at Tk III Dr.Reksodiwiryo Hospital (p-value 0,000 <0.05), compromise strategy (p = 0.017), competency strategy (p = 0.025), accommodation strategy (p = 0,000 ), avoidance strategy (0.017), collaboration strategy (p = 0.021). It is expected that nurses will improve communication within the team and the hospital to be concerned about efforts to improve employee performance satisfaction.